معانى الحركات الإعرابية عند إبراهيم مصطفى - Yani Heryani (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2017)
Ibrahim Musthafa is a lecturer of Nahwu science in Cairo University, Egypt. He is a Nahwu critic in modern century and the first who criticized Qawa’id Nahwiyah Taqlidiyah pioneered by Imam Sibawaih.  He assumed that every feature of I'rab or every harakat I'rab's had a special meaning. According to him, the harakat I'rab’s consists only of dhammah and kasrah, (a) Dhammah is a characteristic of Isnad, ie every word that is the subject of a sentence, it should be read dhammah (rafa '), and belonging to Isnad is mubtada , fa'il and naib fa'il. (b) Kasrah is the character of Idhafah, ie every isim that is located after the huruf idhafah (jaar) and is positioned as mudhaf ilaih then must be read Jaar or khafadh. While fathah is not a feature of I'rab, it is only a harakat that is lightly spoken and liked by the Arabs, and sukun, it is not the character of I'rab because in fact, it is not harakat and it can not be read.